2008
DOI: 10.1262/jrd.19118
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-assisted In Vitro Fertilization of Mouse Oocytes with Spermatozoa Retrieved from Epididymides Stored at 4 Degree C

Abstract: Abstract. This study was performed to investigate the effect of partial zona pellucida incision by piezo micromanipulation (ZIP) on the in vitro fertilizing ability of stored mouse spermatozoa. The storage conditions were optimized by storing the mouse epididymides at 4 C in mineral oil or in the mouse body for up to 4 days after death, and the retrieved spermatozoa were used to fertilize fresh oocytes. No significant difference was observed in fertilization rates between the treatments when epididymides were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Despite recent technological advances, cryopreservation of mammalian oocytes remains difficult, as reflected by reduced rates of fertilization and embryonic development compared with those of fresh oocytes and embryos (Chen et al ., 2001; Larman et al ., 2006; Tian et al ., 2007; Fan et al ., 2008; Li et al ., 2011). In order to improve the efficiency of oocyte cryopreservation, the OPS method for oocyte vitrification was developed subsequently (Vajta et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent technological advances, cryopreservation of mammalian oocytes remains difficult, as reflected by reduced rates of fertilization and embryonic development compared with those of fresh oocytes and embryos (Chen et al ., 2001; Larman et al ., 2006; Tian et al ., 2007; Fan et al ., 2008; Li et al ., 2011). In order to improve the efficiency of oocyte cryopreservation, the OPS method for oocyte vitrification was developed subsequently (Vajta et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the preservation of epididymides by using mineral oil under refrigeration [21,22]. We considered that placing the seminiferous tubules in mineral oil would make them resistant to temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the preservation of sperm under refrigeration have reported optimum temperature control of 4-6°C [11,12,[22][23][24][25]. Furthermore, one study reported that the transportation of C57BL/6 mouse strain epididymides was more successful at 7°C than at 5°C [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low pH and hyperosmotic pressure within the epididymis allow spermatozoa to survive for several days at body temperature (Acott & Carr, 1984; De Pauw et al ., 2003). Recently, some studies on preserving the epididymis at refrigerator temperature (4 °C), to retrieve spermatozoa for in vitro fertilization or artificial insemination, have been carried out in the mouse (Fan et al ., 2008), deer (Hishinuma et al ., 2003; Soler et al ., 2003; Martinez-Pastor et al ., 2005), pigs (Kikuchi K, 1999), dogs (Yu & Leibo, 2002) and sheep (Kaabi et al ., 2003). These results suggest that spermatozoa held within the epididymis are more tolerant for preservation at room temperature than are isolated spermatozoa, but, to our knowledge, there is no report on room temperature preservation of sperm in the epididymis.…”
Section: Introductionmentioning
confidence: 99%